2017
DOI: 10.1039/c7nr06513b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed laser irradiation on gold-coated silver nanoplates and their antibacterial activity

Abstract: Gold-coated silver nanoplates, when subjected to pulsed laser irradiation, changed their shape from triangular to spherical, accompanied by a shift of their extinction spectra. The simple single crystal structure of the silver nanoplates changed to multiple small crystal domains. The ratio of silver to gold of the particles also changed from 22 : 1 to 4.5 : 1, enabling more silver to be released. As a result, the antibacterial activity of the gold-coated silver nanoplates was significantly increased after puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…This shape change is similar to that observed in the gold-coated silver NPLs that we previously reported. 14 Thus, Ag@SiO 2 NPLs melted and changed to a spherical form because of the photothermal effect induced by pulsed laser irradiation. Since spherical silver nanoparticles generally show absorption at about 400 nm, 13 , 14 the color change to yellow shown in Figure 1 is consistent with the shape change to the spherical form by the laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shape change is similar to that observed in the gold-coated silver NPLs that we previously reported. 14 Thus, Ag@SiO 2 NPLs melted and changed to a spherical form because of the photothermal effect induced by pulsed laser irradiation. Since spherical silver nanoparticles generally show absorption at about 400 nm, 13 , 14 the color change to yellow shown in Figure 1 is consistent with the shape change to the spherical form by the laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Concomitantly, silver ions were released from the nanoparticles and exhibited considerable antibacterial activity. 14 Thus, we switched the antibacterial activity from OFF to ON by laser irradiation. Zhu et al also prepared gold-coated silver NPLs and enhanced silver ion release in response to laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Gold-silver alloy nanoparticles have shown their potential to eradicate biofilm and reduce the MICs against Gram-positive and Gram-negative bacteria, which could then be used to circumvent drug resistance ( Ramasamy et al, 2016 ). Kyaw et al (2017) showed that submitting triangular AuNPs coated by silver to laser irradiation, induced a change of shape to spherical and increased the antibacterial activity.…”
Section: Alternative Antibacterial Therapiesmentioning
confidence: 99%
“…The metallic nanoparticles, especially the silver (Ag) nanoparticles have been demonstrated to be effective antibacterial agents with broad antibacterial activity (Agarwal et al, 2010;Mahmoudi and Serpooshan, 2012;Neibert et al, 2012;Durmus and Webster, 2013;Mei et al, 2013;Shah et al, 2013;Agnihotri et al, 2015;Borrelli et al, 2015;Lim et al, 2015;Kyaw et al, 2017;Ximing et al, 2017;Kim et al, 2018;Liu et al, 2018Liu et al, , 2019Gasmalla et al, 2019;Zhang et al, 2019Zhang et al, , 2020He et al, 2020;Horue et al, 2020;Tong et al, 2020). Silver nanoparticles can increase the permeability of bacterial membrane and cell wall and, penetrate into the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the methotrexate (MTX) is also included in the nano-carrier to treat the inflammatory reaction associated with bacterial infection (Lebugle et al, 2002;Alam et al, 2017;Yang et al, 2017;Duan and Li, 2018;Trujillo-Nolasco et al, 2019;Sun et al, 2020). To address the aforementioned issues of bare silver nanoparticles, different nano-carriers have been constructed, such as metalorganic frameworks (MOFs) (Ximing et al, 2017;Zhang et al, 2019Zhang et al, , 2020, hybrid metallic nanoparticles (Mahmoudi and Serpooshan, 2012;Durmus and Webster, 2013;Mei et al, 2013;Shah et al, 2013;Agnihotri et al, 2015;Lim et al, 2015;Kyaw et al, 2017;Kim et al, 2018;Liu et al, 2018;Gasmalla et al, 2019;He et al, 2020;Tong et al, 2020) and mesoporous nanoparticles (Liu et al, 2019). However, the above nano-carriers have some drawbacks, for instance, the low drug loading capacity (<10%) (Cai et al, 2015) and the complexity of designing a multicomponent nano-carrier (containing at least the carrier and two or more compounds).…”
Section: Introductionmentioning
confidence: 99%